2014
DOI: 10.1002/jwmg.733
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary genetic structure of the northern bobwhite west of the Mississippi River

Abstract: We used mitochondrial DNA to study the population structure and genetic diversity of the northern bobwhite (Colinus virginianus) west of the Mississippi River. We observed a lack of phylogeographic structure, high haplotype diversity, and low nucleotide diversity for northern bobwhites in this part of their geographic range. Despite the discordance between geographic patterns of mtDNA diversity and subspecies designations, we detected significant genetic differentiation among 4 subspecies, the plains (C. v. ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 89 publications
1
33
3
Order By: Relevance
“…Regional studies of mtDNA sequence variation in northern bobwhites from southern Texas and the southeastern United States also have found evidence of recent demographic expansion (Wehland 2006, Eo et al 2010, Williford et al 2014c. Previous studies of bobwhites were limited by sampling distribution or sample size, and thus were unable to detect post-Pleistocene expansion, place the results into context with climatic changes, or to estimate the timing and origin of expansion.…”
Section: Genetic Diversity and Historical Demographymentioning
confidence: 99%
See 2 more Smart Citations
“…Regional studies of mtDNA sequence variation in northern bobwhites from southern Texas and the southeastern United States also have found evidence of recent demographic expansion (Wehland 2006, Eo et al 2010, Williford et al 2014c. Previous studies of bobwhites were limited by sampling distribution or sample size, and thus were unable to detect post-Pleistocene expansion, place the results into context with climatic changes, or to estimate the timing and origin of expansion.…”
Section: Genetic Diversity and Historical Demographymentioning
confidence: 99%
“…Studies of reintroduction efforts have found that the introduction of non-native stocks of wild turkey (Meleagris gallopavo) and white-tailed deer (Odocoielus virginianus) altered the genetic structure across the ranges of both species throughout the United States (Leberg et al 1994, Leberg and Ellsworth 1999, DeYoung et al 2003, Mock et al 2004, Latch et al 2006). However, mtDNA phylogeographic analysis of the wild turkey (Mock et al 2002), white-tailed deer (Ellsworth et al 1994a), and the northern bobwhite (Williford et al 2014c) were still able to recover contemporary biogeographic patterns. Aldrich (1946a, b) believed that lack of adaptation to local environments doomed most transplanted wild stocks, and that intermixing of different subspecies had little lasting effect on the plumage and morphology (but see Phillips 1928 andPitelka 1948).…”
Section: Genetic Diversity and Historical Demographymentioning
confidence: 99%
See 1 more Smart Citation
“…To what degree habitat fragmentation and loss have influenced population connectivity, however, is equivocal. Multiple studies over the past decade have evaluated whether restricted gene flow existed among areas within the bobwhite geographic range, suggesting a recent range and population expansion with few dispersal barriers (Evans et al ; Berkman et al ; Williford et al , 2016). However, it is important to note that patterns of genetic differentiation have also been documented at the local scale, possibly due to recent anthropogenic land‐use changes (Berkman et al ).…”
mentioning
confidence: 99%
“…This pattern is supported among multiple avian species, such as the house sparrow ( Passer domesticus ; Kekkonen et al ), black grouse ( Lyrurus tetrix ; Caizergues et al ), white‐tailed ptarmigan ( Lagopus leucura ; Fedy et al ), greater prairie‐chicken ( Tympanuchus cupido ; Johnson et al , 2004), golden‐cheeked warbler ( Setophaga chrysoparia ; Lindsay et al ), white‐breasted wood wren ( Henicorhina leucosticta ), and gray‐headed tanager ( Eucometis penicillata ; Brown et al ). However, despite recent population fragmentation of bobwhites and their presumed low propensity for dispersal (Brennan et al ), several recent studies have documented minimal or low levels of genetic differentiation among bobwhite populations, including among historically recognized subspecies (Eo et al ; Evans et al ; Berkman et al ; Williford et al , 2016). Those studies suggest sufficient gene flow exists across the bobwhite range, and ultimately imply that habitat fragmentation has had little to no effect on their population demographics.…”
mentioning
confidence: 99%